Reviewing and Redefining Relationships: Intergovernmental Relations and Modern Treaty Implementation in Yukon, 1986-2016 - Klein, Rhiannon Beth (2021)
Modern treaties are among the most important legal and constitutional documents in Indigenous affairs in Canada. The treaties created transformative societal change across the North and significantly altered the concepts and understanding of governance. However, the approach taken to implement these foundational accords over the past forty-five years has resulted in strained relations between the Indigenous signatories and their government partners. This study examined the experience of negotiating and implementing modern treaties in Yukon between 1986 and 2016. Drawing on the experiences of three Yukon First Nations and insights provided by 43 former and current negotiators, leaders, implementation staff and other key stakeholders from the federal, territorial and Yukon First Nations governments, this study identified four major findings that should inform future land claims implementation and intergovernmental treaty relations in Yukon and across Canada. First, it was clear that participants cannot underestimate the importance of the implementation process. The negotiation of an agreement is only one step in the overall process; implementation launches a different style and intensity of work. All parties, secondly, need to have a clear understanding of the goals and original intent of the agreements, as well as the historical, political, socio-economic, and cultural contexts that underpin modern treaties as well as those elements that are unique to Yukon. The third finding emphasizes the importance of recognizing that Indigenous peoples are the co-creators of these agreements. These are government-to-government agreements and this should be foundational to their implementation and the approach taken to addressing these modern treaty intergovernmental relations. Finally, instrumental to the successful negotiation of the agreements were the relationships between the parties and the acknowledgement of a common commitment to honour the spirit and intent of the agreements. Critical to the successful implementation ...